2022
DOI: 10.1039/d2cy01045c
|View full text |Cite
|
Sign up to set email alerts
|

Efficient CO2catalytic hydrogenation over CuOx–ZnO/silicalite-1 with stable Cu+species

Abstract: Cu-based/SiO2 nanocatalysts with Cu0 or Cu+ species as active sites have been widely investigated for CO2 hydrogenation. Here, 10CuO/silicalite-1(S-1) and 10CuO-2ZnO/S-1 catalysts were cheap prepared by wet impregnation. 7.5% conversion...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…In addition, the production of oxidized Cu species (Cu 2+ , Cu + , and Cu d+ ) profits from the reduction in Cu size and these oxidized Cu species are thought to be the active sites of methanol production. 24,[57][58][59] Zhou et al found that silica-loaded Cu/ Mo 2 CT x (MXene) catalysts exhibited higher intrinsic methanol production per unit mass of copper than Cu/SiO 2 catalysts with similar copper loading because partial Cu species can migrate to the Mo 2 CT x surface in an atomic-dispersion of Cu d+ , forming silica-loaded Cu/Mo 2 CT x catalysts. 56 The Cu/Mo 2 CT x interface on Cu sites with Lewis acidity is responsible for the enhanced methanol production rate (Fig.…”
Section: Cu-based Catalystsmentioning
confidence: 99%
“…In addition, the production of oxidized Cu species (Cu 2+ , Cu + , and Cu d+ ) profits from the reduction in Cu size and these oxidized Cu species are thought to be the active sites of methanol production. 24,[57][58][59] Zhou et al found that silica-loaded Cu/ Mo 2 CT x (MXene) catalysts exhibited higher intrinsic methanol production per unit mass of copper than Cu/SiO 2 catalysts with similar copper loading because partial Cu species can migrate to the Mo 2 CT x surface in an atomic-dispersion of Cu d+ , forming silica-loaded Cu/Mo 2 CT x catalysts. 56 The Cu/Mo 2 CT x interface on Cu sites with Lewis acidity is responsible for the enhanced methanol production rate (Fig.…”
Section: Cu-based Catalystsmentioning
confidence: 99%
“…In order to further clarify the relative proportions of Cu 0 and Cu + in catalysts with different structures after reduction, the Auger spectra of Cu LMM were collected; Figure 8 shows the results. The spectra were first deconvoluted to two peaks locating at 916.4 eV and 918.5 eV, which were ascribed to the signals of Cu + and Cu 0 species, respectively [20,[24][25][26]. The integration of peak area showed that the ratio of Cu + /(Cu + +Cu 0 ) in reduced CuSi-ae, 65.97%, was evidently higher than 40.42% of Cu + /(Cu + +Cu 0 ) in reduced CuSi-dp.…”
Section: Structural Properties Of Catalystsmentioning
confidence: 99%